The investigation of mechanical properties of B4C-reinforced AlSi7 foams - Uzun, Ari̇f; Turker, Mehmet (Walter de Gruyter GmbH, 2015)
Abstract In this study, the mechanical properties of B4C-reinforced AlSi7 foams produced by using a powder metallurgy method were investigated. For this purpose, Al foams containing B4C at various ratios (0, 2, 4 and 6 %) were prepared with dimensions of 30 × 30 × 14 mm and 110 × 15 × 14 mm for compression and bending tests. Both tests were performed at a 1 mm min–1 strain rate. According to the experimental results, the compressive stress of B4C-reinforced/unreinforced AlSi7 foams, whose relative densities were close to each other, for 10 % strain increased about 15 % with the addition of B4C. Although energy absorption values of B4C-reinforced/unreinforced AlSi7 foams were in a complex correlation for 60 % strain, the amount of absorption energy increased with the increase in relative density and the amount of B4C. Bending strength increased due to strain hardening that occurs with the addition of B4C to AlSi7 foams. While maximum bending strength was 0.9 kN in unreinforced materials, it was ∼1.15 kN in 6 % B4C-reinforced AlSi7 foams. Thus, the bending strength of B4C-reinforced materials is higher by ∼ 28 %.
Keywords: 6. Clean water